Mohr–Coulomb-Model-Based Study on Gas Hydrate-Bearing Sediments and Associated Variance-Based Global Sensitivity Analysis - Chenglang Li; Jie Yuan; Jie Cui; Yi Shan; Shuman Yu (Journal of Marine Science and Engineering, 2025)
Different gas hydrate types, such as methane hydrate and carbon dioxide hydrate, exhibit distinct geomechanical responses and hydrate morphologies in gas-hydrate-bearing sediments (GHBSs). However, most constitutive models for GHBSs focus on methane-hydrate-bearing sediments (MHBSs), while largely overlooking carbon-dioxide-hydrate-bearing sediments (CHBSs). This paper proposes a modified Mohr–Coulomb (M-C) model for GHBSs that incorporates the geomechanical effects of both MHBSs and CHBSs. The model integrates diverse hydrate morphologies—cementing, load-bearing, and pore-filling—into hydrate saturation and incorporates an effective confining pressure. Its validity was demonstrated through simulations of reported triaxial compression tests for both MHBSs and CHBSs. Moreover, a variance-based sensitivity analysis using Sobol’s method evaluated the effects of hydrate-related soil properties on the geomechanical behavior of GHBSs. The results indicate that the shear modulus influences the yield axial strain of the CHBSs and could be up to 1.15 times more than that of the MHBSs. Similarly, the bulk modulus showed an approximate 5% increase in its impact on the yield volumetric strain of the CHBSs compared with the MHBSs. These findings provide a unified framework for modeling GHBSs and have implications for CO2-injection-induced methane production from deep sediments, advancing the understanding and simulation of GHBS geomechanical behavior.